Organizations, Climate Change, and Transparency: Reviewing the Literature on Carbon Disclosure. (March 2015) - Hahn, Rüdiger; Reimsbach, Daniel; Schiemann, Frank
The debate surrounding climate change often centers on companies' contributions to global warming, which has led to an increase in the importance of carbon disclosure. We evaluate the current state of related research and identify its trends, coherences, and caveats via a systematic literature review. Sociopolitical theories of disclosure, economic theories of disclosure, and institutional theory serve as the main theoretical anchors for our exploration. The existing research emphasizes the determinants and, to a lesser extent, effects of carbon disclosure, as well as the associated regulatory issues such as voluntary versus mandatory disclosure. Additionally, we discuss related topics, such as assurance and risks. We find that a large portion of scholarly work provides no link to theory, despite the fact that such links can be identified, for example, from the financial disclosure literature. Finally, we report on the established knowledge and examine the need for additional research.